Itineraries of the Study and Research Group in Ethnomathematics and its Relationship with Mathematics Education - Scandiuzzi, Pedro Paulo [UNESP]; Luebeck, Marcos (Unesp-dept Mathematica, 2011)
This paper outlines the formation, dynamics and some of the paths taken by the Research and Study Group on Ethnomathematics and its relationship with the Graduation Program in Mathematics Education, presenting a history of its formation, its knowing, its doing and its way of being together, and presenting an overview of the research carried out by its members. This paper also addresses the relationship between the group itself with themes within ethnomathematics, highlighting that the group is a space for collective education and cooperative self-education, which takes place through exchange of experiences, sharing of knowledge and in debates and discussions, from being in a group, respecting the reciprocity and valuing alterity, key aspects of ethnomathematics education.
Keywords: Historical of Group; The being/to know/to do/to live together; Ethnomathematics Education